PELAKSANAAN PELAYANAN PUBLIK DI MAL PELAYANAN PUBLIK (MPP) KOTA PEKANBARU PADA SAAT PANDEMI COVID-19 TAHUN 2020-2021 - Fitri Nurzana; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The existence of the COVID-19 pandemic which resulted in the reluctance of people to leave the house and restrictions on the movement of people to leave the house with the closure of several roads leading to the Pekanbaru City MPP which resulted in difficulty in managing the Pekanbaru City MPP. This study aims to:(1) To find out public services at the Pekanbaru City Public Service Mall (MPP) to the public during the COVID-19 pandemic in 2020-2021 and (2) To find out the inhibiting factors in the implementation of public services at the Public Service Mall ( MPP) Pekanbaru City to the public during the COVID-19 pandemic in 2020-2021. The theory used in this research is the theory of the principles of public service according to the Decree of the Ministry of Administrative Reform and Bureaucratic Reform (KEMENPAN RB) Number 63/2003 as follows: Transparency, Accountability, Conditional, Participatory, Equality of rights and balance of rights and obligations. Data collection used in this research is by interview and documentation. This research was carried out at the Pekanbaru City Public Service Mall. The results showed that the implementation of public services at the Pekanbaru City MPP complies with the applicable rules, namely Pekanbaru Mayor Regulation Number 104 of 2020 concerning Guidelines for New Life Behavior for Productive and Safe Communities in the Prevention and Control of Corona Virus Disease 2019 (Covid-19). The implementation of orderly services using health protocols and the Protect Care application. The operational hours of the Pekanbaru City MPP are limited both in terms of operating hours and also the number of people served. Keywords: Public Service Mal (MPP), Public Service, Covid-19 Pandemic